Flood exposure of environmental assets - G. Bertoli; C. Arrighi; E. Caporali (Natural Hazards and Earth System Sciences)
Environmental assets provide important benefits to society and support the equilibrium of natural processes. They can be affected by floods; however, flood risk analyses usually neglect environmental areas due to (i) a lack of agreement on what should be considered an environmental asset, (ii) a poor understanding of environmental values, and (iii) the absence of damage models. The aim of this work is to advance the understanding of environmental exposure to river floods by first identifying asset typologies that could be considered in flood risk analyses and second by introducing a method, named EnvXflood, to estimate flood exposure qualitative values of environmental assets. The method is structured around three levels of detail requiring increasing information, from a fast and minimal-resource analysis suitable for regional assessment to a detailed ecosystem-service-based site analysis. Exposure focuses on the social and environmental value of the assets. Social values were investigated by means of a participatory approach. The method was tested on three case studies in Italy (the Tuscany region, Chiana Basin, and Orcia Basin). The ecosystem service weighting obtained from the participatory approach highlights the perceived leading importance of the biodiversity-supporting service. The results of the analyses show that environmental assets related to water, such as rivers, lakes, and wetlands, are the most exposed to floods. However, they are commonly not considered exposed assets in typical river management practices. Further research should aim at consolidating the asset typologies to be included in environmental exposure analysis and their social and ecological value, moving towards a coherent understanding of environmental flood impacts.